A Qualitative Study of Rural Primary Care Clinician Views on Remote Monitoring Technologies. Issue 1 (24th May 2013) - Davis, Melinda M.; Currey, Jillian M.; Howk, Sonya; DeSordi, Molly R.; Boise, Linda; Fagnan, Lyle J.; Vuckovic, Nancy
Abstract Purpose Remote monitoring technologies (RMTs) may improve the quality of care, reduce access barriers, and help control medical costs. Despite the role of primary care clinicians as potential key users of RMTs, few studies explore their views. This study explores rural primary care clinician interest and the resources necessary to incorporate RMTs into routine practice. Methods We conducted 15 in‐depth interviews with rural primary care clinician members of the Oregon Rural Practice‐based Research Network (ORPRN) from November 2011 to April 2012. Our multidisciplinary team used thematic analysis to identify emergent themes and a cross‐case comparative analysis to explore variation by participant and practice characteristics. Results Clinicians expressed interest in RMTs most relevant to their clinical practice, such as supporting chronic disease management, noting benefits to patients of all ages. They expressed concern about the quantity of data, patient motivation to utilize equipment, and potential changes to the patient‐clinician encounter. Direct data transfer into the clinic's electronic health record (EHR), availability in multiple formats, and review by ancillary staff could facilitate implementation. Although participants acknowledged the potential system‐level benefits of using RMTs, adoption would be difficult without payment reform. Conclusions Adoption of RMTs by rural primary care clinicians may be influenced by equipment purpose and functionality, implementation resources, and payment. Clinician and staff engagement will be critical to actualize RMT use in routine primary care.